Selective Regulation of Cytoskeletal Dynamics and Filopodia Formation by Teleost Leukocyte Immune-Type Receptors Differentially Contributes to Target Capture During the Phagocytic Process - Lillico, Dustin M. E.; Pemberton, Joshua G.; Stafford, James L. (Frontiers in Immunology, 2018)
Phagocytosis evolved from a fundamental nutrient acquisition mechanism in primitive unicellular amoeboids, into a dynamic and complex component of innate immunity in multicellular organisms. To better understand the cellular mechanisms contributing to phagocytic processes across vertebrates, our research has focused on characterizing the involvement of innate immune proteins originally identified in channel catfish (Ictalurus punctatus) called leukocyte immune-type receptors (IpLITRs). These unique teleost proteins share basic structural as well as distant phylogenetic relationships with several immunoregulatory proteins within the mammalian immunoglobulin superfamily. In the present study, we use a combination of live-cell confocal imaging and high-resolution scanning electron microscopy to further examine the classical immunoreceptor tyrosine-based activation motif (ITAM)-dependent phagocytic pathway mediated by the chimeric construct IpLITR 2.6b/IpFcRγ-L and the functionally diverse immunoreceptor tyrosine-based inhibitory motif (ITIM)-containing receptor IpLITR 1.1b. Results demonstrate that IpLITR 1.1b-expressing cells can uniquely generate actin dense filopodia-like protrusions during the early stages of extracellular target interactions. In addition, we observed that these structures retract after contacting extracellular targets to secure captured microspheres on the cell surface. This activity was often followed by the generation of robust secondary waves of actin polymerization leading to the formation of stabilized phagocytic cups. At depressed temperatures of 27oC, IpLITR 2.6b/IpFcRγ-L-mediated phagocytosis was completely blocked, whereas IpLITR 1.1b-expressing cells continued to generate dynamic actin-dense filopodia at this lower temperature. Overall, these results provide new support for the hypothesis that IpLITR 1.1b, but not IpLITR 2.6b/IpFcRγ-L, directly triggers filopodia formation when expressed in representative myeloid cells. This also offers new information regarding the directed ability of immunoregulatory receptor-types to initiate dynamic membrane structures and provides insights into an alternative ITAM-independent target capture pathway that is functionally distinct from the classical phagocytic pathways.